Electrochemical Biosensor Composed of Silver Ion‐Mediated dsDNA on Au‐Encapsulated Bi2Se3 Nanoparticles for the Detection of H2O2 Released from Breast Cancer Cells. Issue 16 (24th March 2018) - Mohammadniaei, Mohsen; Yoon, Jinho; Lee, Taek; Bharate, Bapurao G.; Jo, Jinhee; Lee, Donghyun; Choi, Jeong‐Woo
Abstract: A newly developed electrochemical biosensor composed of a topological insulator (TI) and metallic DNA (mDNA) is fabricated. The bismuth selenide nanoparticle (Bi2 Se3 NP) is synthesized and sandwiched between the gold electrode and another Au‐deposited thin layer (Bi2 Se3 @Au). Then, eight‐silver‐ion mediated double‐stranded DNA (mDNA) is immobilized onto the substrate (Bi2 Se3 @Au‐mDNA) for the further detection of hydrogen peroxide. The Bi2 Se3 NP acts as the electrochemical‐signal booster, while unprecedentedly its encapsulation by the Au thin layer keeps the TI surface states protected, improves its electrochemical‐signal stability and provides an excellent platform for the subsequent covalent immobilization of the mDNA through Au–thiol interaction. Electrochemical results show that the fabricated biosensor represents much higher Ag + redox current (≈10 times) than those electrodes prepared without Bi2 Se3 @Au. The characterization of the Bi2 Se3 @Au‐mDNA film is confirmed by atomic force microscopy, scanning tunneling microscopy, and cyclic voltammetry. The proposed biosensor shows a dynamic range of 00.10 × 10 −6 m to 27.30 × 10 −6 m, very low detection limit (10 × 10 −9 m ), unique current response (1.6 s), sound H2 O2 recovery in serum, and substantial capability to classify two breast cancer subtypes (MCF‐7 and MDA‐MB‐231) based on their difference in the H2 O2 generation, offering potential applications in the biomedicine and pharmacology fields. Abstract : Bi2 Se3 nanoparticle encapsulated between the two layers of gold, owing to its unique electrical properties, is found to enhance the electrochemical signal of silver ion intercalated inside the DNA helix and increase the signal‐to‐noise ratio of the proposed biosensor. The Bi2 Se3 @Au‐mDNA biosensor offers an unrivaled current response (1.6 s) and a low limit of detection (10 × 10 −9 m ).